Culture of terrorism - Chomsky, Noam (London, 1988)
The central and not very surprising-conclusion that emerges from the documentary and historical record is that the U.S. interna tional and security policy, rooted in the structure of power in the domestic society, has as its primary goal the preservation of what we might call the "Fifth Freedom," understood crudely but with a fair degree of accuracy as the freedom to rob, to exploit and dominate, to undertake any course of action to ensure that existing privilege is protected and advanced. This guiding principle was overlooked when Franklin Delano Roosevelt announced the Four Freedoms that the U.S. and its allies would uphold in the conflict with fascism: freedom of speech, freedom of worship, freedom from want, and freedom from fear.
Keywords: United States - Foreign relations - 1981